Lake ice coverage from Långa Harrsjön, 2025 - Abisko Scientific Research Station (Swedish Polar Research Secretariat, 2026)
Observation of ice coverage of the SITES Water lakes.
Abisko Scientific Research Station (2026). Lake ice coverage from Långa Harrsjön, 2025 [Data set]. Swedish Infrastructure for Ecosystem Science (SITES). https://hdl.handle.net/11676.1/mOws_xHDxoq3KHCWVHbTflqJ
Keywords: Abisko Scientific Research Station; Lake ice; Lake ice breakup; Lake ice freeze; Year; Year; Time period in days of ice coverage; Time period in days of ice coverage; Soil Science; Markvetenskap; Agriculture, Forestry and Fisheries; Jordbruk, skogsbruk och fiske; Agricultural Science; Jordbruksvetenskap; Ecology; Ekologi; Multidisciplinary Geosciences; Multidisciplinär geovetenskap; Environmental Sciences; Miljövetenskap; Climate Science; Klimatvetenskap